Transformasi Metode Dakwah pada Era Algoritma Media Sosial - Anja Kusuma Atmaja (ANWARUL, 2026)
Social media algorithms have transformed the ecology of Islamic preaching by determining visibility, engagement, and audience segmentation across various digital platforms. This article aimed to review the scientific literature on how TikTok, Instagram, and YouTube algorithms shape Islamic broadcasting methods. This study used a qualitative literature review of recent journal articles, books, and proceedings published between 2018 and 2024. The analysis focused on four aspects, namely algorithmic logic and its theoretical foundations, content adaptation strategies by Islamic preachers, dynamics of audience reception and engagement, and ethical implications for Islamic communication. The results of the review show that algorithms encourage the presentation of short, emotional, and visual preaching messages, accelerate the platformization of religion, shift authority from institutional ulama to digital influencers, and generate ethical challenges such as clickbait and the commodification of religion. The conclusion of this review confirms that digital Islamic preaching requires adaptive digital literacy and critical awareness of how algorithms work without abandoning Islamic ethical principles, particularly tabligh, amanah, and hikmah. This review contributes to the development of a conceptual framework for integrating algorithmic critique into Islamic communication studies.